Kepatuhan Pelaporan E-Faktur 3.0 Berdasarkan Persepsi Efikasi Diri, Kebermanfaatan, dan Kemudahan - Felani, Maulana Robbi; Fidiana, Fidiana (Jurnal Kajian Akuntansi, 2022)
AbstractThis study aims to test the impact of the perceived self-efficacy, the usefulness, and the convenience toward electronic periodic tax return (e-SPT) of electronic value added tax (VAT) reporting. This study is quantitative research. The data are collected by distributing questionnaires to 121 participants, they are directors, supervisor, and accountant staffs of the companies which are considered as the VAT enterprise. in East Java and has used e-invoice version 3.0 for the reporting of e-SPT VAT period. Research instruments in the form of questionnaires with 7 (seven) questions for self-efficacy variables 10 (ten) question indicators for perception of usefulness as well as perception ease of use. The analysis of this study applies the multiple linier regression method. As a result, statistical tests support the hypothesis that perception of self-efficacy and ease perception improve compliance of e-VAT reporting. Meanwhile, the perception of usefulness has no effect on compliance of e-VAT reporting. This finding provides confirmation that e-Invoice 3.0 is a new application so that taxpayers as users are still in the process of adapting the use of the application so that many additional features that cannot be maximum utilized by the taxpayer in the short term.Keywords: Ease of use; Electronic periodic tax return; Perceived self-efficacy; Usefulness; VATÂ Abstrak Penelitian ini bertujuan untuk menguji pengaruh persepsi efikasi diri, persepsi kebermanfaatan, dan persepsi kemudahan terhadap kepatuhan pelaporan e-SPT masa PPN berbasis e-Faktur 3.0. Jenis penelitian ini adalah penelitian kuantitatif. Pengumpulan data menggunakan kuesioner dengan responden sejumlah 121 orang yang terdiri dari direktur, supervisor maupun staf akuntansi yang terdaftar sebagai Pengusaha Kena Pajak di Jawa Timur dan telah menggunakan e-faktur versi 3.0 untuk pelaporan e-SPT masa PPN. Instrumen penelitian berupa kuesioner dengan 7 (tujuh) pertanyaan untuk variabel efikasi diri, 10 (sepuluh) indikator pertanyaan untuk persepsi kebermanfaatan dan persepsi kemudahan penggunaan. Metode analisis data yang digunakan adalah analisis linier berganda. Hasil uji statistik mendukung hipotesis bahwa persepsi efikasi diri dan persepsi kemudahan meningkatkan kepatuhan pelaporan e-SPT masa PPN. Sementara itu, persepsi kebermanfaatan tidak berpengaruh terhadap kepatuhan pelaporan e-SPT masa PPN. Temuan ini memberikan konfirmasi bahwa e-Faktur 3.0 merupakan aplikasi baru sehingga wajib pajak sebagai pengguna masih dalam proses adaptasi penggunaan aplikasi sehingga banyak fitur tambahan yang belum bisa dimanfaatkan secara maksimal oleh wajib pajak. Artinya, manfaat aplikasi e-Faktur belum bisa dirasakan dalam jangka pendek.Kata Kunci: e-SPT masa PPN; Kegunaan; Kenyamanan; Persepsi Kemudahan Penggunaan